Space Security System using Motion Sensor and Notification of Short Message Service with Arduino-Based Fuzzy Logic Algorithm - Erlan, Darmawan; Rivandi, Taufan (2019)
Security system is a store generally still use a conventional security system. Conventional security devices used include padlock and Close Circuit Television (CCTV). CCTV devices have a function to record any activity or event as long as the store is active or outside of its activity hours. However, CCTV has disadvantages because CCTV only records without giving a notification if there is human movement in the room after the store's operating hours end. Therefore we need a security system that can provide up-to-date information in real time to detect human movements within the store when it is outside its operating hours. The system was built using Passive InfraRed Sensors (PIR) which are connected to the microcontroller as the central control system to detect human movement s outside the store's operating hours based on the results of design and testing, this system can be used properly and provides real time notifications to users. When the sensor detects human movement outside the store's operating hours, the system will send an SMS notification to the shop owner's mobile number.